Statement from the Biomedicine Programme Leads - Sara Namvar, Tahmina Hussain, Matthew Jones, Pika Miklavc (BioScientist: The Salford Biomedicine Society Magazine, 2024)
Hear from the Biomedicine Programme Leaders at the University of Salford, as they welcome students, returning and new. Explore the achievements of the Biomedicine Department and discover what to look forward to, in this academic year.